1983
DOI: 10.1113/jphysiol.1983.sp014758
|View full text |Cite
|
Sign up to set email alerts
|

Inferior olive inactivation decreases the excitability of the intracerebellar and lateral vestibular nuclei in the rat.

Abstract: SUMMARY1. In rats under sodium pentobarbitone anaesthesia the inferior olive region has been reversibly inactivated by applying a cooling probe to the ventral surface of the medulla. Unitary activity has been recorded from the fastigial, interpositus and Deiters nuclei.2. Identification of units was based on the presence of a dye spot, left by the recording micropipette. In the Deiters nucleus, an additional criterion ofidentification was the antidromic activation from spinal cord stimulation.3. Following cool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…When the stimulation resumed, CRs were immediately absent on the background of already suppressed IN activity. This stimulation-independent and NBQX-induced suppression of IN firing rate is consistent with previous reports of the tonic effects of blocking IO input to the cerebellum (Benedetti et al, 1983;Bengtsson et al, 2004). It appears that NBQX downregulated the firing rate of the IO and this upregulated the activity of Purkinje cells in the cerebellar cortex (Batini et al, 1985;Lang, 2001;Bengtsson et al, 2004).…”
Section: Involvement Of the Io In Expression Of Crs: Tonic Dysfunctiosupporting
confidence: 80%
See 2 more Smart Citations
“…When the stimulation resumed, CRs were immediately absent on the background of already suppressed IN activity. This stimulation-independent and NBQX-induced suppression of IN firing rate is consistent with previous reports of the tonic effects of blocking IO input to the cerebellum (Benedetti et al, 1983;Bengtsson et al, 2004). It appears that NBQX downregulated the firing rate of the IO and this upregulated the activity of Purkinje cells in the cerebellar cortex (Batini et al, 1985;Lang, 2001;Bengtsson et al, 2004).…”
Section: Involvement Of the Io In Expression Of Crs: Tonic Dysfunctiosupporting
confidence: 80%
“…Authors of these behavioral studies speculated that a tonic dysfunction of the cerebellar circuit could explain this effect. Specifically, they suggested that CR deficits were caused by a nonspecific tonic suppression of activity in cerebellar nuclei that is known to be associated with IO lesions/inactivations (Benedetti et al, 1983;Zbarska et al, 2007). These findings were challenged by reports that lesioning (McCormick et al, 1985) or inactivating (Medina et al, 2002) the IO produces not an immediate, but gradual, extinction-like suppression of CRs.…”
Section: Involvement Of the Io In Expression Of Crs: Tonic Dysfunctiomentioning
confidence: 57%
See 1 more Smart Citation
“…The results of inferior olive inactivation, however, argue against this possibility. As reported previously (Benedetti et al 1983;Batini et al 1985), inactivation of the inferior olive increases the level of tonic Purkinje cell simple spike activity (Fig. 5).…”
Section: Role Of the Cerebellum In Trigeminal Reflex Blinkssupporting
confidence: 54%
“…Despite the low rate, climbing fiber discharge strongly influences Purkinje cell simple spike discharge, and elimination of olivary input causes simple spike discharge to rapidly increase to a high regular rate (Colin et al, 1980;Rawson and Tilokskulchai, 1981;Montarolo et al, 1982;Strata and Montarolo, 1982). Simple spike discharge inhibits cerebellar nuclear cells (Ito et al, 1964), so a high rate of simple spike discharge effectively turns off cells in the cerebellar nuclei (Benedetti et al, 1983), which reduces discharge in cerebellar targets such as the magnocellular red nucleus (RNm) (Bardin et al, 1983;Billard and Daniel, 1985). Although the previous studies relied on anesthetized preparations, it is likely that the circuit operates in a similar fashion in the awake animal, since blocking glutamate receptors in the IO reduces discharge in the cerebellar nuclei of conscious rabbits (Zbarska et al, 2008).…”
Section: Introductionmentioning
confidence: 99%